A Pragmatic Approach to Getting Published: 35 Tips for Early Career Researchers - Glover, Natasha M.; Antoniadi, Ioanna; George, Gavin M.; Götzenberger, Lars; Gutzat, Ruben; Koorem, Kadri; Liancourt, Pierre; Rutowicz, Kinga; Saharan, Krishna; You, Wanhui; Mayer, Philipp (Frontiers in Plant Science, 2016)
It is trite to say “publish or perish,” yet many early career researchers are often at a loss on how to best get one’s work published. With strong competition and many manuscripts submitted, it is difficult to convince editors and reviewers to opt for acceptance. A pragmatic approach to publishing may increase one’s odds of success. Here, we-- a group of postdocs in the field of plant science-- present specific recommendations for early career scientists on advanced levels. We cannot provide a recipe-like set of instructions with success guaranteed, but we come from a broad background in plant science, with experience publishing in a large number of different journals of varying topics and impact factors. We provide tips, tricks, and tools for collaboration, journal selection, and achieving acceptance.